APPLICATION OF THE TAGUCHI METHOD TO SELECT THE OPTIMUM CUTTING PARAMETERS FOR TANGENTIAL CYLINDRICAL GRINDING OF AISI D3 TOOL STEEL - Ozay, Cetin; Ballikaya, Hasan; Savas, Vedat (Inst Za Kovinske Materiale I in Tehnologie, 2016)
The purpose of this research was an analysis of the optimum cutting conditions for the lowest surface roughness in tangential cylindrical grinding of the AISI D3 tool steel using the Taguchi method. In this experimental investigation, the surface roughness with various wheel speeds, workpiece speeds, feed rates and depths was observed. The surface roughness was investigated employing the Taguchi design of experiments and an analysis of variance (ANOVA). Significant machining parameters were identified using the signal-to-noise ratio. The results of the experiments indicate that the wheel speed and feed rate have dominating effects on the surface roughness during the cutting. The developed new grinding process can be used in the machining industries in order to determine the optimum cutting parameters for the minimum surface roughness.
Keywords: tangential cylindrical grinding; Taguchi method; surface roughness; ANOVA